Sistema informático de control de medicamentos en el seguro social campesino de la comunidad El Junco del cantón Tosagua - Mora Macías, María Valeria (2013)
The main objective of this research was to create a computer system in order to improve the control of drugs in the Rural Social Security Junco community Tosagua Canton, with the firm intention to expedite the process of drug registration delivered to each of the members of this clinic. The software model was used for the preparation of the application was the waterfall model, which allowed the collection of information to define the requirements and system architecture. Was prepared dataflow diagram which helped to describe the functionality of the system. Then he proceeded to develop the database in SQL Server 2008, which was coupled to the treatment and handling of information. Following this GUI was developed and incorporated system of the application logic by encoding, for the effect is the development platform used Microsoft Visual Basic 2010. Once validated system function was verified use with satisfaction, seeing that optimizes and streamlines the process of drug control register rural social security.